Preliminary Results of a Screening Programme for Chlamydia in an Asymptomatic Young Population in Spain - Yuguero, Oriol; Fernández-Armenteros, Jose Manuel; Vilela, Álvaro; Aramburu, Jesús; Laín, Raquel; Godoy, Pere (Frontiers in Public Health, 2021)
Introduction Chlamydia trachomatis (CT) infection has increased in recent years, reaching 127 million cases in 2016. Possible complications, especially among women, require intervention for early detection of the infection. The objective of our study was to determine the prevalence of CT infection in a young, sexually active, asymptomatic population. Methods A cross-sectional study was conducted between December 2017 and 31 December 2018 among young patients aged 18 to 25 years attending the emergency room for any reason. The presence of CT and other STIs in urine was determined by the Allplex Nucleic Acid Amplification Test (NAAT) with a urine sample. All patients testing positive were followed by the STD unit and tests on all sexual partners/contacts were offered. Moreover we obtained data about sexual habits and risk factors via a self-reporting questionnaire. Results 1308 patients were eligible for inclusion of whom 298 consented to participate. Of these, 22/298 (7.4%) were diagnosed with CT. Young people with two or more sexual partners in the last month and those suffering from infection by ureaplasma were at greater risk of infection by CT. Up to 50% of participants do not use barrier methods Conclusion The prevalence of infection by CT in the asymptomatic young population is higher than expected according to the recent literature in Spain. The scarce use of barrier methods among this population may be one of the causes of this increase and one of the targets to work on in order to reduce the prevalence of the infection.